Skogskullens förskola; the reggio Emilia approach and the built environment - Nordström, Märta (My University, 2025)
Many children spend their preschool years in temporary barracks with uninspiring architecture and insufficient outdoor spaces. This thesis establishes that as a problem and aims to contribute a hopeful addition to the current preschool discourse by taking knowledge from Reggio Emilia pedagogics and its approach to the built environment. The proposal strives to create inspiring educational architecture with joyful and elegant elements. The project proposal is a wooden preschool, located in Tynnered, southern Gothenburg. It fits eight departments, or approximately 150 children. The project leans on the Reggio Emilia ideas surrounding natural materials and trusting children with maintaining their space. Methods used to develop the project are research for design through literature studies, site visits, and the studying of reference objects. Research has also been conducted through the iterative design process, using models and drawings. The project has grown out of the Reggio Emilia pedagogical philosophy and landed in the cultural context of the site. Conclusions drawn from this project have been surrounding the connections between architecture and pedagogics, and how they can coexist and cooperate without being too restrictive. A problem the thesis has tried to overcome was the balance between an economically defensible project while still creating valuable architecture. AMunicipal guidelines have been considered alongside the Reggio Emilia philosophy, and in situations where they contradict each other, the Reggio Emilia philosophy has been allowed to challenge the municipal guidelines in order to develop the current preschool architectural discourse.
Keywords: Children, Reggio Emilia, Preschool architecture, Wood buildings